Post-Socialist Peasant? - Kaneff, D. author. aut Link
IX, 225 p.
Keywords: During the past decade, life in post-socialist states has been fraught with instability and conflict. This book focuses on changing rural-urban relations - and growing divisions between them - in the context of the reforms. Contributions to this volume explore responses to capitalist-oriented policies and reasons for rural disenfranchisement. The work takes an ethnographic approach to exploring how 'global' processes engage with local, rural concerns in the post-socialist world.